(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of the study was to know the number of cases of RIF pain presentation to General Surgery Department and the number of cases of appendicitis out of presented RIF pain Cases. Study Design: Case series study Place and Duration of Study: This study was conducted at the Department of General Surgery, Bannu Medical College Bannu from December 2016 to May 2017. Materials and Methods: Records of patients aged 5-60+ years from surgical unit and Operation theater of DHQ teaching hospital were reviewed. Results: Total number of cases presented with right iliac fossa pain along with nausea vomiting were 220 containing 57.7% Males and 42.3% females. Out of those 194 were diagnosed as Acute appendicitis of which 108(55.6%) and 86(44.3%) were male and female cases respectively. Acute appendicitis was mostly seen in teenagers with percentage of 49.9% collectively. Perforated cases recorded were 30% and rate of negative appendectomy was 16.6% overall. During study period not asingle mortality associated with appendicitis wasseen. Conclusion: Acute appendicitis was mostly seen in Teenage Group i.e 11-19 years old. Delay in diagnosis lead to perforated appendicitis leading to emergency and increase in complications. Most of the cases belonged to low socioeconomic class.